Measuring potential anthropogenic impacts on Icelandic killer whales (Orcinus Orca) through scar-based analysis - Lionnet, Laetitia Anne Marie Gabrielle, 1995- (2020)
Verkefnið er lokað til 17.06.2021. Human marine activities around the world have been increasingly noticed as responsible for negative impacts on marine animals. Through a photographic analysis, the scars on Icelandic killer whale dorsal fins and saddle patches were counted and classified, in order to have an overview of the potential anthropogenic impacts affecting these cetaceans. Indeed, entanglement in fishing gear and boat strikes are common issues affecting a number of cetaceans every year and the tightly intertwined daily life of killer whales and fishermen of Iceland gives sense to this study. The results of the scar-based analysis showed a minimum entanglement estimate of 8.98% and a minimum boat strike estimate of 3.24% for killer whales in Iceland. There were significant differences in line scars, rake marks and notches for males and females with proportionally more male individuals affected. There were significant differences in line scars and rake marks for individuals of different diet; putative prey switching whales being more affected than presumed herring specialists. There was a significant difference in notches between adults and juveniles where adults were more affected than juveniles. The entanglement results are considered low as compared to the results for a similar study on Icelandic humpback whales suggesting either that the issue is less important for smaller cetaceans, or that the identification of scars cannot be done as easily for killer whales as for humpback whales for physical reasons. The study suggests an introduction of specific fishing gear to reduce the occurrence of entanglement events as well as speed regulations to limit vessel strikes. Further research should include fishermen’s or sailors’ observations of anthropogenic interactions, but also a veterinarian’s help to effectively identify disease-related scars. Skaðsemi sjávarútvegs á lífríki sjávar hefur í auknum mæli vakið athygli á heimsvísu. Til þess að fá yfirsýn yfir þessa hugsanlegu skaðsemi af mannavöldum, hafa ...